PENGARUH KONSENTRASI ASAM FOSFAT DAN BERAT SEMEN PUTIH SEBAGAI ADSORBEN DALAM PEMURNIAN CRUDE GLISEROL - Lestari Lestari; Made Arsa; I Wayan Suirta (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
The research of purification process of crude glycerol using phosphoric acid and white cement as adsorbent has been carried out. The aim of this research was to study the effect of phosphoric acid concentration and weight of white cement used as adsorbent in the purification process to the purity of glycerol. The research was done by the addition phosphoric acid in crude glycerol followed by adsorption with white cement. Glycerol quality parameters were determined by assesment of glycerol density, viscosity, and by comparing its GC-MS spectra to GC-MS spectra of standard glycerol. The result showed that purification process of glycerol using 5 % phosphoric acid and 5 grams of white cement gave the highest level of glycerol which was 84.20%. The density of purified glycerol obtained in this research was 1.2595 ± 3.1622 x 10-5 g/mL, the viscosity was 1.4372 ± 3.8333 x 10-3 Pa.s, and the GC_MS spectra purified glycerol showed similar fragmentation pattern and retention time with the glycerol standard.